Acut Effect of sodium chlorid on the crustacean Acanthocyclops bicuspidatus (Claus) (Copepoda: Cyclopoida) - Bassat, S.F.; Sadeq, SH. A.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study deals with the effect of acute exposure of different salt concentrations of NaCl on male and female of                     IU.FOBRJMOPNARJ, which belongs to Class Copepoda, Order Cyclopoida by calculating lethal concentration killing 50% (LC50), lethal concentration killing 100% (LC100) and safe concentration (LC0).     The results showed that LC50 values were 3.80ppt, 2.75ppt and 2.29 ppt for males during 24,48 and 72 hrs. exposure respectively while LC50 values were 2.45ppt, 2.18ppt and 1.77ppt for females for the same periods of exposure.      The lethal concentration (LC100) values were 5ppt for males and 4ppt for females for 24hrs. exposure. On the other hand the safe concentration (LC0) was 1ppt for both males and females for the same periods of exposure.